2017
DOI: 10.1111/jdi.12686
|View full text |Cite
|
Sign up to set email alerts
|

Safety, tolerability and efficacy of lixisenatide in combination with oral antidiabetic treatment in Japanese patients with type 2 diabetes: An open‐label, multicenter study

Abstract: Aim/IntroductionTo assess the overall safety and efficacy of lixisenatide in combination with background oral antidiabetic drug treatment in Japanese patients with type 2 diabetes, as required by Japanese guidelines.Materials and MethodsA phase 3, multicenter, uncontrolled, open‐label, four‐arm, parallel‐group study of Japanese outpatients with type 2 diabetes was carried out; patients received once‐daily lixisenatide in combination with biguanide, thiazolidinedione, alpha‐glucosidase inhibitors or glinide (NC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 24 publications
1
1
0
Order By: Relevance
“…The incidence of nausea/vomiting in the present study was consistent with some previous studies of Japanese patients treated with lixisenatide. However, in patients treated with liraglutide, the present study showed a high incidence of nausea/vomiting compared with previous studies in which the occurrence of GI AEs was reported to be 44–60%, of which nausea occurred in 5–14%.…”
Section: Discussionsupporting
confidence: 91%
“…The incidence of nausea/vomiting in the present study was consistent with some previous studies of Japanese patients treated with lixisenatide. However, in patients treated with liraglutide, the present study showed a high incidence of nausea/vomiting compared with previous studies in which the occurrence of GI AEs was reported to be 44–60%, of which nausea occurred in 5–14%.…”
Section: Discussionsupporting
confidence: 91%
“…Many injectable therapies of the glucagonlike peptide 1 (GLP-1) receptor agonist (RA) class (including semaglutide, dulaglutide, exenatide, liraglutide, and lixisenatide) have also been developed and approved for use in Japan [10][11][12][13][14][15][16][17]. In addition, a new oral formulation of semaglutide has been investigated in Japanese patients with T2D [18,19].…”
Section: Introductionmentioning
confidence: 99%